The Internationalisation of Service Firms: The Impact of Value Creation on the Internationalisation Strategy of Firms - Denitsa Hazarbassanova Blagoeva (Copenhagen Business School (CBS), 2016)
The question the thesis aims at resolving is: How do the value creation logics of firms impact their internationalisation? The overall aim of this PhD project is to explore and test an approach to understanding the internationalisation of service firms, based not on opposing them to manufacturing ones, looking at descriptive service characteristics nor industry effects, but on the way they create value. Why and how are service firms different? and What are the drivers behind their internationalisation? are the questions motivating this PhD project. It explores if the value creation specificities may be universal axes around which all MNCs, both manufacturing and service ones, configure themselves internally and externally across geographic locations. We do not in fact know that services are different from manufacturing - some empirical evidence suggests they are (e.g. Laanti, McDougal and Baume, 2009), some - that they are not (e.g., Terpstra and Yu, 1988). What we do know is that services are very important. They generate roughly 80% of GDP in the United States and the European Union, and the proportion is well over 50% in most countries, industrial and developing alike (International Monetary Fund, the World Bank and OECD, 2014). The attention to internationalisation of services has significantly increased and yet, many questions remain open (e.g. Pla-Barber and Ghauri, 2012).
hdl:10398/9369
Keywords: 650